2020
DOI: 10.3390/medicina56020087
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Biomarkers for Magnetic Resonance Imaging Diagnosis of Traumatic Brain Injury

Abstract: Background and Objectives: The annual global incidence of traumatic brain injury (TBI) is over 10 million. An estimated 29% of TBI patients with negative computed tomography (CT−) have positive magnetic resonance imaging (MRI+) findings. Judicious use of serum biomarkers with MRI may aid in diagnosis of CT-occult TBI. The current manuscript aimed to evaluate the diagnostic, therapeutic and risk-stratification utility of known biomarkers and intracranial MRI pathology. Materials and Methods: The PubMed database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…Levels of GFAP within the serum have been linked to ensuing gross brain pathology, such as lesions, contusions and hemorrhages 45 , however, as our cFPI model of mTBI in micro pigs does not produce such focal injuries 29 , the change in serum GFAP following cFPI cannot be associated with gross pathologies. Clinical studies have demonstrated that the levels of circulating GFAP within the first day post-injury could also be associated with the presence of more subtle pathologies, including DAI [21][22][23] . Experimental blast-wave-induced TBI has also shown associations with elevated GFAP serum levels 46 , however, a clinical study found a negative correlation between serum GFAP levels and www.nature.com/scientificreports/ blast TBI 47 , highlighting the complexity of serum biomarker investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of GFAP within the serum have been linked to ensuing gross brain pathology, such as lesions, contusions and hemorrhages 45 , however, as our cFPI model of mTBI in micro pigs does not produce such focal injuries 29 , the change in serum GFAP following cFPI cannot be associated with gross pathologies. Clinical studies have demonstrated that the levels of circulating GFAP within the first day post-injury could also be associated with the presence of more subtle pathologies, including DAI [21][22][23] . Experimental blast-wave-induced TBI has also shown associations with elevated GFAP serum levels 46 , however, a clinical study found a negative correlation between serum GFAP levels and www.nature.com/scientificreports/ blast TBI 47 , highlighting the complexity of serum biomarker investigations.…”
Section: Discussionmentioning
confidence: 99%
“…changes in parenchymal GfAp indicate subtle thalamic astrocyte pathophysiology and correlate with circulating GfAp levels. While, the utility of GFAP as a biomarker of gross pathological change is clearly established 16,17 , the relationship between serum GFAP levels and more subtle diffuse histopathology, especially within the thalamus, remains promising, but limited [21][22][23][24] . The cFPI model does not produce contusion in our hands 29,43 and therefore also does not produce a gliotic scar in which astrogliosis is apparent and homogenously localized at the time point assessed.…”
Section: Morphological Features Of Acute Microglia/macrophage Activatmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon neuronal damage, neurofilaments that are discharged into the interstitial fluid subsequently diffuse into the cerebrospinal fluid (CSF) and then the blood 10 . Elevated levels of neurofilaments are general indicators of axonal damage in many neurological conditions, including multiple sclerosis, 11 HIV‐associated encephalopathy, 12 neurodegenerative disorders, 13 aging, 14 stroke, 15 and traumatic brain injury 16 . Increased levels of NFL are evident well before the clinical onset of cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
“…10 Elevated levels of neurofilaments are general indicators of axonal damage in many neurological conditions, including multiple sclerosis, 11 HIV-associated encephalopathy, 12 neurodegenerative disorders, 13 aging, 14 stroke, 15 and traumatic brain injury. 16 Neurofilaments levels and tau protein are, therefore, used as surrogate markers of axonal damage. To our knowledge, this study is the first to investigate the levels of NFL and tau protein in patients with plaque-type psoriasis, their correlation to disease severity and their relationship with other clinical and biochemical characteristics of psoriasis.…”
Section: Introductionmentioning
confidence: 99%